2017
DOI: 10.1038/srep41609
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Current and Future Freshwater Flood Risk from North Atlantic Tropical Cyclones via Insurance Claims

Abstract: The most recent decades have witnessed record breaking losses associated with U.S. landfalling tropical cyclones (TCs). Flood-related damages represent a large portion of these losses, and although storm surge is typically the main focus in the media and of warnings, much of the TC flood losses are instead freshwater-driven, often extending far inland from the landfall locations. Despite this actuality, knowledge of TC freshwater flood risk is still limited. Here we provide for the first time a comprehensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 32 publications
1
50
0
1
Order By: Relevance
“…Although HCWL and river peaks may be caused or influenced by the same event, they may not occur on the same day. Hence, a time window is required to consider this effect (Berghuijs et al, 2019;Czajkowski et al, 2017;Merz et al, 2018;Rowe & Villarini, 2013). Flood peaks that occur within a window of ±7 days typically belong to the same large-scale event (Merz et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Although HCWL and river peaks may be caused or influenced by the same event, they may not occur on the same day. Hence, a time window is required to consider this effect (Berghuijs et al, 2019;Czajkowski et al, 2017;Merz et al, 2018;Rowe & Villarini, 2013). Flood peaks that occur within a window of ±7 days typically belong to the same large-scale event (Merz et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall and freshwater flooding from tropical cyclones (TCs) have caused large numbers of fatalities and vast economic damage (Rappaport 2000(Rappaport , 2014Czajkowski et al 2011Czajkowski et al , 2013Czajkowski et al , 2017Rezapour and Baldock 2014), and they have been shown to play an important role in controlling the upper tail of flood distributions in the eastern United States (Smith et al 2011;Villarini and Smith 2010). Moreover, TC rainfall may significantly increase in the future due to likely increases of atmospheric moisture content and potential changes of storm activity (Knutson and Tuleya 2004;Knutson et al 2010Knutson et al , 2013Villarini et al 2014a;Emanuel 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example in southern California and Arizona, moisture from TC‐events interacted with mid‐latitude disturbances such as troughs or cut‐off lows and produced locally heavy rainfall enhanced by the orography in the region (e.g., Smith, ; Farfan and Zehnder, ; Corbosiero et al ., ; Ritchie et al ., ; Wood and Ritchie, ). Most economic losses and fatalities due to TCs in the United States are found near the coast; yet recent studies have shown similar destructive floods that occur in inland riverine basins far from the coast as moisture from landfalling TCs produces substantial rainfall in those regions (e.g., Villarini et al ., ; Czajkowski et al ., ; Aryal et al ., ). In the southwestern United States, heavy rain and devastating flash floods in inland basins were caused by Tropical Storm Kathleen (1976) in southern California and by the entrainment of moisture from the remnants of Tropical Storm Octave (1983) in southeastern Arizona (Smith, ; Hjalmarson, ; Roeske et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Flood losses due to tropical cyclones (TCs) are responsible for numerous fatalities and significant economic losses estimated in the billions of dollars (e.g., Czajkowski et al ., ; ; Rappaport, ). In the United States, the majority of TCs make landfall along the eastern Seaboard, the Florida Peninsula, and the Gulf of Mexico, while far fewer eastern North Pacific TCs make landfall in the western United States.…”
Section: Introductionmentioning
confidence: 99%